Noncanonical writings and New Testament interpretation - Evans, Craig A. 1952- (Hendrickson, 1992)
Perhaps one of the most challenging hurdles facing the NT interpreter is becoming familiar with the ancient primary sources from the countless Greco-Roman, Jewish, and Pagan works. From the Paraphrase of Shem to Pesiqta Rabbati, scholars and students alike must have a fundamental understanding of these documents' content, provenance, and place in NT interpretation. Unfortunately, achieving even an elementary facility with this literature has in the past depended on either years of experience or a photographic memory. Now Craig A. Evans pulls together the essentials of date, language, text and translations, and general bibliography. He also evaluates the material's relevance for interpreting the NT. Six appendixes, including a list of quotations, allusions, and parallels to the NT, and a comparison of Jesus' parables with those of the rabbis, are designed to further save the interpreter hours of precious time.
Keywords: Bible. -- N.T. -- Extra-canonical parallels; Dead Sea Scrolls -- Relation to the New Testament; Qumrantexte; Bibel -- Neues Testament; Apokryphen; Apocryphes - Critique, interprétation, etc; Jodendom; Klassieke oudheid; Littérature rabbinique - Relation avec le Nouveau Testament; Nieuwe Testament; Antike; Bibel. Neues Testament; Judentum; Apocryphal books -- Criticism, interpretation, etc; Rabbinical literature -- Relation to the New Testament; Einleitung